Neutrophil dysregulation is pathogenic in idiopathic inflammatory myopathies - Seto, Nickie; Torres-Ruiz, Jose Jiram; Carmona-Rivera, Carmelo; Pinal-Fernandez, Iago; Pak, Katherine; Purmalek, Monica M.; Hosono, Yuji; Fernandes-Cerqueira, Catia; Gowda, Prateek; Arnett, Nathan; Gorbach, Alexander; Benveniste, Olivier; et al. (JCI insight, 2020)
Idiopathic inflammatory myopathies (IIM) are characterized by muscle inflammation and weakness, myositis-specific autoantibodies (MSAs), and extramuscular organ damage. The role of neutrophil dysregulation and neutrophil extracellular traps (NETs) in IIM is unclear. We assessed whether pathogenic neutrophil subsets (low-density granulocytes [LDGs]) and NETs were elevated in IIM, associated with clinical presentation and MSAs, and their effect on skeletal myoblasts and myotubes. Circulating NETs and LDGs were quantified and correlated with clinical measures. Specific MSAs were tested for their ability to induce NETs. NETs and neutrophil gene expression were measured in IIM biopsies. Whether NETs damage skeletal myoblasts and myotubes was tested. Circulating LDGs and NETs were increased in IIM. IIM LDGs had an enhanced ability to form NETs. LDGs and NETs correlated with IIM disease activity and muscle damage. The serum MSA anti-MDA5 correlated with circulating and tissue NETs and directly enhanced NET formation. An enhanced neutrophil gene signature was present in IIM muscle and associated with muscle injury and tissue IFN gene signatures. IIM NETs decreased the viability of myotubes in a citrullinated histone-dependent manner. Dysregulated neutrophil pathways may play pathogenic roles in IIM through their ability to directly injure muscle cells and other affected tissues.